Analisis Status Resistensi Aedes aegypti terhadap Insektisida Cypermethrin 0,05% di Kecamatan Endemis Kabupaten Malang - Siti Mariyatul Qibtiyah; Moh. Mirza Nuryady; Rr. Eko Susetyarini; Tutut Indria Permana; Dhiga Agung Sasongkojati (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Aedes aegypti mosquitoes was the primary vector for carrying dengue fever. Dengue vector control has been widely carried out to reduce the number of dengue cases in Indonesia, but resistance cases have occurred in several areas, so it was necessary to know the status of resistance to determine appropriate efforts to control the vector. The purpose of this study was to determine the resistance status of Aedes aegypti in Malang Regency to 0.05% Cypermethrin. This type of research was descriptive observational research. The research method used was the susceptibility method with WHO standards using impregnated paper with the insecticide 0.05% Cypermethrin. Aedes aegypti mosquitoes were obtained from ovitrap results in the form of eggs and larvae taken from rearing at the Chemical Laboratory of the University of Muhammadiyah Malang. The number of mosquitoes used was 400 mosquitoes of the Aedes aegypti species aged 3-5 days. Mosquitoes were contacted with impregnated paper 0.05% Cypermethrin for one hour and held for 24 hours. Based on WHO standards, the criteria for susceptibility were determined as follows: said to be vulnerable if mortality was >98%, said to be tolerant if mortality was between 80-98%, and said to be resistant if mortality was <80%. The results showed that Aedes aegypti in Malang Regency was tolerant to 0.05% Cypermethrin with death rate each district; Turen 90%, Kepanjen 90%, Karangploso 96%, and Dau 100%, with percentage of 94%. This research showed that Cypermethrin with a concentration of 0.05% was still effective in reducing the development of Aedes aegypti, but the rotation of use must still be considered to reduce the number of dengue cases.